Photocatalytic decomposition of A549-lung cancer cancer cells by TiO2 nanoparticles. (2021) - Balachandran, K.; Mageswari, S.; Preethi, A.
Abstract: A novel, less time consuming and cost ineffective Wet chemical technique (WCT) was used to synthesis TiO2 nanoparticles at relatively low temperature, in acidic pH, using Titanium tetra isopropoxide (TTIP) as a precursor. The synthesized nanoparticles were characterized by XRD, SEM, TEM, and Uv–Visible spectroscopy. The results shows that the particle size from 17 nm to 14 nm. The Uv–Visible spectra show that blue shift was observed in TiO2 nanoparticles. The TEM images revealed that all the particles were in nanometer size. The synthesized nanoparticles shows good photocatalytic activity and it decompose 85% of A549 (lung cancer) cells in 4 h reaction.